2010
DOI: 10.3168/jds.2010-3295
|View full text |Cite
|
Sign up to set email alerts
|

Blood profiles in dairy cows with displaced abomasum

Abstract: An observational study was carried out in Swedish dairy herds to investigate differences between cows with and without displaced abomasum (DA), in concentrations of glucose, insulin, fructosamine, nonesterified fatty acids (NEFA), β-hydroxybutyrate, cholesterol, haptoglobin, increased enzyme activity of aspartate aminotransferase and glutamate dehydrogenase, and the revised Quantitative Insulin Sensitivity Check Index (RQUICKI). A secondary aim was to study how blood profiles for DA cows vary with time in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
49
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 35 publications
12
49
0
3
Order By: Relevance
“…This dehydration could be the result of a lack of intake and failure to absorb fluids from the proximal gastrointestinal tract due to partial or complete obstruction. In the leukogram, some researchers found increased numbers of leukocytes and neutrophelia (Stengärde et al 2010). They attributed these changes to immunological responses against endotoxemia and abomasitis that may occur secondarily to LDA (Stengärde et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dehydration could be the result of a lack of intake and failure to absorb fluids from the proximal gastrointestinal tract due to partial or complete obstruction. In the leukogram, some researchers found increased numbers of leukocytes and neutrophelia (Stengärde et al 2010). They attributed these changes to immunological responses against endotoxemia and abomasitis that may occur secondarily to LDA (Stengärde et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In the leukogram, some researchers found increased numbers of leukocytes and neutrophelia (Stengärde et al 2010). They attributed these changes to immunological responses against endotoxemia and abomasitis that may occur secondarily to LDA (Stengärde et al 2010). In the study reported here, only otherwise healthy cows were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study there was only mild hypokalemia without metabolic alkalosis. Biochemical profiles reflecting energy balance, hepatic function, and inflammatory response are used for the evaluation of peripartum diseases in cows (14). In cows that develop displacement of the abomasum, ketosis may be an important risk factor (3).…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation of fatty acids in the liver predisposes the cow to the induction of ketosis accompanied by an elevation of serum betahydroxybutyrate (b-HOB). Various authors have already demonstrated that the blood levels of b-HOB, NEFA and calcium (Ca) are closely correlated with the incidence of production diseases ( Hoedemaker et al, 2004;Goff, 2006;Stengärde et al, 2010;Chapinal et al, 2012Chapinal et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%